2022
DOI: 10.1002/appl.202200096
|View full text |Cite
|
Sign up to set email alerts
|

Enabling LiNO3 in carbonate electrolytes by flame‐retardant electrolyte additive as a cosolvent for enhanced performance of lithium metal batteries

Abstract: Most contemporary liquid Li‐ion battery chemistries are based on carbonate electrolytes, however, these typically perform poorly with metallic lithium. Especially, when only a small reservoir of metal is present, cells fail quickly due to the complete consumption of electrochemically active Li. Electrolyte modification is, therefore, a commonly chosen strategy to increase cycling stability and prolong lifetime of the cell. At the same time, complete redevelopment of an electrolyte usually creates a new set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Previous studies reported that lithium nitrate (LiNO 3 ) as electrolyte additive was a valid path to strengthen the interface stability for dendrite suppression [ 22 , 23 ]. The LiNO 3 has been proved to be critical electrolyte additive for Li–S batteries in restraining the “shuttle effect” of lithium polysulfides and improving interfacial stability of Li metal anode [ 29 32 ]. The NO 3 − will degrade into Li + conductors, Li 3 N and LiN x O y , which are beneficial for Li plating/stripping behavior [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that lithium nitrate (LiNO 3 ) as electrolyte additive was a valid path to strengthen the interface stability for dendrite suppression [ 22 , 23 ]. The LiNO 3 has been proved to be critical electrolyte additive for Li–S batteries in restraining the “shuttle effect” of lithium polysulfides and improving interfacial stability of Li metal anode [ 29 32 ]. The NO 3 − will degrade into Li + conductors, Li 3 N and LiN x O y , which are beneficial for Li plating/stripping behavior [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have focused on strategies to improve the solubility of LiNO 3 in carbonate electrolytes. [29][30][31][32][33][34][35][36] Other approaches, including plasma activation, sputtering, coating, and printing, among others, aimed at pre-forming a Li 3 N layer on the surface of Li foil prior to cycling, have also been explored. [37][38][39][40][41][42][43][44][45][46] Zhu et al 45 reported a thin Li composite anode based on an AlN-embedded reduced graphene oxide (rGO) scaffold via one-step molten Li infusion.…”
mentioning
confidence: 99%